2017
DOI: 10.1093/mnras/stx2996
|View full text |Cite
|
Sign up to set email alerts
|

Triggering active galactic nuclei in galaxy clusters

Abstract: We model the triggering of Active Galactic Nuclei (AGN) in galaxy clusters using the semi-analytic galaxy formation model SAGE (Croton et al. 2016). We prescribe triggering methods based on the ram pressure galaxies experience as they move throughout the intracluster medium, which is hypothesized to trigger star formation and AGN activity. The clustercentric radius and velocity distribution of the simulated active galaxies produced by these models are compared with that of AGN and galaxies with intense star fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
31
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 88 publications
(169 reference statements)
6
31
0
4
Order By: Relevance
“…Despite radio AGN being principally observed in galaxy clusters they could be equally abundant in all galaxies, which would be in good agreement with recent LOFAR source counts (Krause et al 2019). Much of the halo gas could also be stripped when the Milky Way will merge into the Virgo cluster (Tully et al 2014), perhaps reinforced by simultaneous AGN triggering (Marshall et al 2018).…”
Section: Discussionsupporting
confidence: 81%
“…Despite radio AGN being principally observed in galaxy clusters they could be equally abundant in all galaxies, which would be in good agreement with recent LOFAR source counts (Krause et al 2019). Much of the halo gas could also be stripped when the Milky Way will merge into the Virgo cluster (Tully et al 2014), perhaps reinforced by simultaneous AGN triggering (Marshall et al 2018).…”
Section: Discussionsupporting
confidence: 81%
“…Dynamical modeling of LOFAR radio source populations in the HETDEX field by Hardcastle et al (2019) found some tentative evidence for a higher fraction of short-lived sources at low luminosities, potentially reflecting different jet triggering mechanisms for different radio source populations, as previously suggested by numerous authors (e.g. Pimbblet et al 2013;Kaviraj et al 2015;Marshall et al 2018;Krause et al 2019a).…”
Section: Jet Triggering Mechanismsmentioning
confidence: 57%
“…Later studies based on X-ray data (Pimbblet et al 2013) did not however confirm this result, showing comparable fractions of AGN in cluster and field, though there may be an effect related to distance from the cluster centre (Ehlert et al 2014). In this context, Marshall et al (2018) used semi-analytic galaxy evolution models to show that both star formation and AGN can be triggered by the ram pressure as they move through the intracluster medium, in galaxies located at distances from the cluster centre larger than the virial radius; at smaller distances, where the ram pressure is higher, models suggest that the gas is stripped from the galaxy and can't feed the AGN. Ramos-Martínez et al (2018) analyzed the role of the galactic magnetic field in the gas stripping using 3D magnetohydrodynamic simulations: they found that the magnetic field can contribute to generate a gas inflow to the central parts of the galaxies, triggering star formation and maybe feeding the AGN.…”
Section: Introductionmentioning
confidence: 88%